(untitled) (Journal of Educational Sciences, 2016)
The paper studies the relationship between the concepts of «potential», «intellect», «intellectual potential» and «intellectual capital», «mentality». Considered in detail the approaches of domestic and foreign psychology and pedagogy. Attention is focused on Kazakhstan works on research of various types of capacity. In particular, describe the scientific school N.E. Pfeiffer, considered in detail the idea of the cognitive psychology of Russian authors. Intellectual potential is closely connected with the cognitive demand of the individual. Types of capacities - personal, axiological, constructive, communicative, creative, and others. The country’s intellectual potential accumulated for decades and centuries; is a principal means of development of the nation, «tool» of the progress of the society, its culture development. Intellectual potential of the nation has several components. It includes the objective of the system, enterprises and organizations, as well as directly subjective components, the collection of personal potentials. The essential basis of intelligence and intellectual capital are the intellectual knowledge. All changes to the data knowledge lead to the appropriate modified forms of intellectual capital, which is the basis for his new substantial characteristics and assessments. Essential aspect of such characteristics is the structure of intellectual capital.